Optimization Of Bread Production Quantity At The “Fadila Kitchen” Bakery - Verdyani, Putri Vabilla; Shanty, Baroya Mila; Putri, Viajeng Purnama (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research was conducted in the Fadila Kitchen bakery industry which produces various breads and desserts. The purpose of this research is to determine the planning of bread production quantities based on company policy, planning of bread production quantities based on aggregate planning, and the best production quantities for the company in order to produce minimum production costs with final inventory not piling up. The research was conducted using the Aggregate Planning method with demand forecasting using the exponential smoothing with trend method. The research results show that calculations using aggregate planning result in lower production costs and final inventory results do not accumulate compared to planning based on company policy. The advice given to Fadila Kitchen is that the company can carry out aggregate planning by forecasting demand to determine production quantities and adjust machine operations according to existing capacity in order to reduce excess production and a pileup of finished products.